Safety and efficacy of single-balloon enteroscopy in management of gastrointestinal bleeding in patients with a left ventricular assist device - Koul, Abhinav; Pham, Donald M.; Nanda, Arjun; Woods, Kevin E.; Keilin, Steven D. (Endoscopy International Open, 2017)
Background and study aims Left ventricular assist devices (LVADs) are currently the standard of care in treatment of patients with end-stage heart failure waiting for heart transplant as well as destination therapy for non-transplant candidates. However, patients with LVADs are at increased risk of gastrointestinal bleeding due to the device’s unique effects on hemodynamics. A major source of gastrointestinal bleeding in these patients are gastrointestinal angioectasias located within the small bowel that can only be reached with deep enteroscopy. The goal of our study was to determine the safety and efficacy of single-balloon enteroscopy (SBE) in treating gastrointestinal bleeding in patients with LVADs. Patients and methods We present a retrospective case series performed on patients with LVADs who underwent SBE to treat episodes of gastrointestinal bleeding. All procedures were performed at Emory University Hospital by a single endoscopist. Patient demographics, diagnosis and treatment of gastrointestinal bleeding, episodes of re-bleeding, and procedure-related complications were examined.Results A total of 27 SBE procedures performed in 14 patients were reviewed. SBE was performed in an antegrade approach in 89 % (24/27) of cases. Deep intubation was achieved in all antegrade procedures, with the distal jejunum reached in 79 % (19/24) of cases. The diagnostic yield was 78 %. There were no reported complications associated with the procedures.Conclusions SBE is a safe and effective modality to manage gastrointestinal bleeding in patients with LVADs.